whoishRisk – an R package to calculate WHO/ISH cardiovascular risk scores for all epidemiological subregions of the world [version 2; referees: 2 approved, 1 approved with reservations] - Dylan Collins; Joseph Lee; Niklas Bobrovitz; Constantinos Koshiaris; Alison Ward; Carl Heneghan (F1000Research, 2017)
The World Health Organisation and International Society of Hypertension (WHO/ISH) cardiovascular disease (CVD) risk assessment charts have been implemented in many low- and middle-income countries as part of the WHO Package of Essential Non-Communicable Disease (PEN) Interventions for Primary Health Care in Low-Resource settings. Evaluation of the WHO/ISH cardiovascular risk charts and their use is a key priority and since they only existed in paper or PDF formats, we developed an R implementation of the charts for all epidemiological subregions of the world. The main strengths of this implementation are that it is built in a free, open-source, coding language with simple syntax, can be downloaded from github as a package (“whoishRisk”), and can be used with a standard computer.